Spectroscopic investigation of bioactive constituents in extracts of citri reticulatae and spica prunella - Chow Tan, Wei (Universiti Sains Malaysia, 2009)
Traditional Chinese Herbal Medicines (TCHMs) are getting more and more popular nowadays in the whole world for improving health condition of human beings as well as preventing and healing diseases. Pericarpium Citri reticulatae and Spica Prunella vulgaris were chosen for this study as they are widely used in Traditional Chinese Medicine. The objective of this project is to investigate the bioactive constituents of such herbal extracts using spectroscopic method. Prior to the instrumental analysis, preliminary phytochemical screening of both herbs was performed according to the standard protocols reported in literature. The UV-Visible spectral investigations of n-hexane and hot water extracts of Citri reticulatae indicated conjugation of C=O, -COOR, C=N, N=N, -COOH, -N02 or - CONH2• Similar trends were observed in the case of methanol, hot water and n-hexane extract of Spica prunella. The UV-Visible spectral data was correlated to the FT-IR spectral bands recorded over the 4000- 400 cm-1 range. The FT-IR results indicated presence of the functional groups that can be attributed for polyphenols, alkane groups, condensed system of aromatic rings and ester groups in Citri reticulatae and Spica prunella. The flame atomic absorption determinations carried out for copper, iron and zinc were 0.034 ± 0.002 mg L-1, 0.372 ± 0.006 mg L-1 and 0.081 ± 0.002 mg L-1 respectively in Citri reticulatae and 0.136 ± 0.003 mg L-1, 3.211 ± 0.061 mg L-1 and 0.400 ± 0.006 mg L-1 in Spica prunella. The levels of heavy metals such as cadmium were below the detection limits, except for lead which was present in Spica prunella at a concentration of 0.317 ± 0.009 mg L- 1• The concentration of all the elements detected was within the safe limits set by WHO.